2015
DOI: 10.1038/pr.2015.50
|View full text |Cite|
|
Sign up to set email alerts
|

The association between linoleic acid levels in colostrum and child cognition at 2 and 3 y in the EDEN cohort

Abstract: Background: Breastfeeding has been associated with improved cognitive development. This may be explained by polyunsaturated fatty acid (PUFA) content of breast milk, especially long-chain (LC) PUFA that are needed for postnatal brain growth. Methods: Using data from the French EDEN cohort, we aimed to study whether the PUFA content of colostrum may explain observed associations between breastfeeding duration and cognitive scores at 2 and 3 y. A total of 709 breastfed children with available data on PUFA compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 37 publications
2
47
1
Order By: Relevance
“…Several cohort studies reported a negative relation between maternal n-6/n-3 PUFAs status and infant and child neurodevelopment assessed by various tests [4, 79] and these reports partly confirmed our results. The Seychelles Child Development Nutrition Study (SCDS) [4] reported that maternal n-6/n-3 PUFAs in serum was negatively associated with the BSID-II PDI at 9 months of age but not at 30 months.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Several cohort studies reported a negative relation between maternal n-6/n-3 PUFAs status and infant and child neurodevelopment assessed by various tests [4, 79] and these reports partly confirmed our results. The Seychelles Child Development Nutrition Study (SCDS) [4] reported that maternal n-6/n-3 PUFAs in serum was negatively associated with the BSID-II PDI at 9 months of age but not at 30 months.…”
Section: Discussionsupporting
confidence: 91%
“…The Seychelles Child Development Nutrition Study (SCDS) [4] reported that maternal n-6/n-3 PUFAs in serum was negatively associated with the BSID-II PDI at 9 months of age but not at 30 months. The EDEN mother-child cohort in France showed that maternal dietary n-6/n-3 PUFAs intakes among never-breastfed children were negatively associated with the MacArthur Communicative Development Inventory (CDI) at 2 years of age and with the ASQ at 3 years of age [8], while the n-6/n-3 PUFAs in colostrum among breastfed children was negatively associated with the ASQ at 3 years of age [9]. Recently, the Generation R study in the Netherlands [7] demonstrated that a higher maternal plasma n-3/n-6 PUFAs was associated with fewer emotional problems in children at 6 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations